Digital tools to facilitate intraoperative coronary artery bypass graft patency assessment. - Balacumaraswami, L; Taggart, D (2004)
Intraoperative graft failure is an important cause of cardiac mortality and morbidity. Hence, verification of graft patency should be one of the most important aspects of coronary artery bypass grafting. Although several techniques have been advocated to assess intraoperative graft patency, there is no unanimously accepted method. Intraoperative fluorescence imaging is a novel technique based on the fluorescence of indocyanine green dye, which provides real-time visual images of graft flow in the operating room. Transit-time flowmetry is based on the ultrasound principle and provides mean graft flow and derived values such as pulsatility index. This article describes the usefulness and limitations of various techniques in general and summarizes the current knowledge with the use of these two techniques in the setting of intraoperative coronary artery bypass graft patency assessment.